PERAN SERTA ORANG TUA DAN SEKOLAH DALAM PEMBENTUKAN KARAKTER RELIGIUS MELALUI POLA PEMBIASAAN (Maslahah: Journal of Islamic Studies, 2024)
Schools hold the main control in building the character and attitude of early childhood to teach them religious attitudes and habitual patterns to possess the morality of noble character (akhlaqul karimah). Therefore, the religious school program activities can integrate school, family, and environmental activities with the hope of enhancing the character formation of children. This research was conducted to see how the religious attitude formed through habituation and to know the results of the formation of the religious character of early childhood through habituation. The approach was carried out using a qualitative descriptive method to show the current state without using numerical data, but by providing clear information based on post-positivism philosophy. The results of the study show the fact that the formation of religious character through habitual patterns in the "Pelangi Harapan" playgroup can improve the behavior of students for the better.
Keywords: Character Formation; Religious Values; Habituation Patterns